A Novel Crosslinking Method for Improving the Anti-Calcification Ability and Extracellular Matrix Stability in Transcatheter Heart Valves - Qi, Xiaoke; Jiang, Zhenlin; Song, Mingzhe; Tang, Zhenjie; Xie, Xinlong; Liu, Yuhong; Wu, Qiying; Wu, Zhongshi (Frontiers in Bioengineering and Biotechnology, 2022)
More than 200,000 patients with aortic disease worldwide undergo surgical valve replacement each year and transcatheter heart valve (THV) have been widely used than ever before. However, THV made by the glutaraldehyde (Glut) crosslinking method has the disadvantages of being prone to calcification , which significantly reduces the durability of biomaterials. In this study, we applied a novel crosslinking method using ribose in THV for the first time, which can decrease calcification and increase the stability of the extracellular matrix (ECM). We incubated the bovine pericardium (BP) in ribose solution at 37°C with shaking for 12 days and confirmed that the structure of BP was more compact than that of the Glut group. Moreover, the ribose method remarkably enhanced the biomechanical properties, provided reliable resistance to enzymatic degradation and satisfactory cellular compatibility in THV. When BP was implanted subcutaneously in vivo, we demonstrated that ECM components were preserved more completely, especially in elastin, and the immune inflammatory response was more moderate than that in the Glut treatment group. Finally, the ribose-crosslinked materials showed better anti-calcification potential and improved durability of THV than Glut-crosslinked materials.